Unmasking The Culprit: Recurrent Nosebleeds From Masson’s Tumor - Awan, Javeria; Masood, Sundas; Akaash, Haitham; Chaudhary, Sadia (Journal of Rawalpindi Medical College, 2026)
Masson’s tumor, also called Intravascular papillary endothelial hyperplasia (IPEH), is a benign condition affecting various parts of the body; nonetheless, sinonasal cavity involvement is uncommon. We present the case of a 32-year-old male who experienced recurrent epistaxis and frontal headaches for 13 years. Despite multiple nasal surgeries, his symptoms persisted without a confirmed diagnosis. Physical examination revealed numerous adhesions near the middle turbinate, which were more pronounced on the left side. A contrast-enhanced CT scan revealed a heterogeneously enhancing soft-tissue lesion in the left maxillary sinus that extended into the nasal cavity, with erosion of the sinus walls. Histopathology confirmed Masson’s tumor. The patient underwent several surgeries, including lateral rhinotomy and excision of a fleshy mass in the maxillary cavity. One-year post-surgery, there was no recurrence or re-bleeding. IPEH of the sinonasal region should be part of the differential diagnosis of recurrent epistaxis; otherwise, it can present an ENT surgeon with a diagnostic conundrum. Keywords: Nasal cavity, Epistaxis, Maxillary sinus, Nasal surgical procedures, Vascular malformations